Brainstem volume changes in myalgic encephalomyelitis/chronic fatigue syndrome and long COVID patients - Thapaliya, Kiran; Marshall-Gradisnik, Sonya; Barth, Markus; Eaton-Fitch, Natalie; Barnden, Leighton (Frontiers in Neuroscience, 2023)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and long COVID patients have overlapping neurological, autonomic, pain, and post-exertional symptoms. We compared volumes of brainstem regions for 10 ME/CFS (CCC or ICC criteria), 8 long COVID (WHO Delphi consensus), and 10 healthy control (HC) subjects on 3D, T1-weighted MRI images acquired using sub-millimeter isotropic resolution using an ultra-high field strength of 7 Tesla. Group comparisons with HC detected significantly larger volumes in ME/CFS for pons (p = 0.004) and whole brainstem (p = 0.01), and in long COVID for pons (p = 0.003), superior cerebellar peduncle (p = 0.009), and whole brainstem (p = 0.005). No significant differences were found between ME/CFS and long COVID volumes. In ME/CFS, we detected positive correlations between the pons and whole brainstem volumes with “pain” and negative correlations between the midbrain and whole brainstem volumes with “breathing difficulty.” In long COVID patients a strong negative relationship was detected between midbrain volume and “breathing difficulty.” Our study demonstrated an abnormal brainstem volume in both ME/CFS and long COVID consistent with the overlapping symptoms.